Stature estimation from long bone lengths in a Thai population - Mahakkanukrauh P. (2014)
The estimation of stature is a very important step in developing a biological profile for forensic identification. However, little previous work has been done on stature estimation among modern Thai people, despite a growing number of forensic cases in Thailand in recent years. The current study was carried out on a sample of 200 skeletons from a northern Thai population (132 males and 68 females), ranging in age from 19 to 94 years. The maximum lengths of six long bones (humerus, radius, ulna, femur, tibia and fibula) were measured and stature reconstruction formulae generated using linear regression. These equations were then tested on a holdout sample of 15 females and 15 males. Results reveal that the three lower limb bones are the most accurate estimators of stature among the males, with the fibula equation producing the lowest standard error of the estimate (SE = 4.89. cm), followed by the femur (SE = 5.06. cm). Results for females were mixed. The femur produced the lowest standard error among the females (SE = 5.21. cm), followed by the radius (SE = 5.63. cm). However, when tested against the holdout sample (n= 30), the femur equations were considerably more accurate, with a mean absolute error of 3.5. cm and a median absolute error of 2.4. cm. Females exhibited a higher standard error of the estimate than reported in many previous studies. This higher error may be the result of a recent secular trend in stature affecting the females of our sample somewhat more than the males. © 2011 Elsevier Ireland Ltd.